The influence of information-based initiatives and negotiated environmental agreements on technological change - Nicholas Askounes Ashford (Fondazione Eni Enrico Mattei (FEEM), 1997)
Polluting firms must have the willingness, opportunity, and capacity or capability to undertake technological changes to improve their environmental performance. These changes could involve the adoption (diffusion) of already-proven technologies, or require incremental to radical innovation. This paper addresses the likely effects on technological change of a variety of so-called "voluntary approaches" to environmental problems including eco-labeling; eco-audits; pollution reporting requirements; the negotiation of emission, effluent, waste and technology-based standards for compliance; innovation waivers; negotiation of the means and timetable for coming into compliance; and the inclusion of pollution prevention/cleaner production in enforcement agreements. The capability to change depends on both the inherent innovativeness of the firm and available economic resources. The outcomes of various strategies will necessarily differ, depending on whether they create incentives which encourage firms (1) to investigate here-to-fore unrecognized environmental problems and to act on information the firm already has (as a result of being required to report emissions, effluents, and waste; by seeking to earn a product eco-label; by undertaking eco-audits, or by negotiating the means and timetable for coming into compliance), (2) to search for information outside the firm regarding already-existing solutions, thus encouraging the diffusion of technology from other firms or industries (as a result of performing technology options analysis), or (3) to undertake incremental technological innovation, or more radical innovation if they can (as a result of applying for innovation waivers, negotiating compliance levels or technology-based standards with regulatory agencies, or negotiating pollution prevention/cleaner production agreements with regulatory authorities). It is important to think about what kind of technological change is needed to address an environmental problem and who is in the best position to deliver it. Sometimes it must be acknowledged that the firms creating the problems are not capable of providing the needed or best solutions, and a new entrant must displace the polluting firm or technology.
Keywords: 330; Technischer Fortschritt; Umweltschutz; Selbstverpflichtung; Theorie